The burden of breast cancer in Poland: current status and future directions - Sierocki, Wojciech; Kornowska, Ligia; Dudek, Alicja; Szpakowicz, Małgorzata; Dompe, Claudia; Roszak, Magdalena (Frontiers in Oncology, 2025)
Breast cancer poses a significant public health challenge in Poland, with incidence rates exceeding the EU average and a concerning disparity between incidence and mortality. This review analyzes the key steps of breast cancer diagnosis and treatment in Poland, examining factors influencing therapeutic outcomes. We explore the complex interplay of epidemiological trends, prevention strategies, the impact of the National Oncology Strategy (NSO) and the National Cancer Network (KSO), access to care challenges, treatment protocols, and drug programs. While Poland has made strides in implementing comprehensive care pathways, including the DiLO card system and dedicated drug programs, significant gaps remain. Low screening participation, delays in diagnosis, limited access to innovative therapies, and reimbursement restrictions hinder optimal patient outcomes. This review highlights the urgent need for targeted interventions to address these challenges, improve early detection, enhance access to care, and ultimately reduce the burden of breast cancer for Polish patients.